INVESTIGATING THE SUNDANESE TRADITIONAL CUISINE PROPER NAMES THROUGH COGNITIVE LINGUISTIC STUDY FOR SUNDANESE LANGUAGE LEARNING - Citraresmana, Elvi; Susilawati, Lusi; Hermandra, Hermandra (English Review: Journal of English Education, 2022)
This research investigated the Sundanese traditional cuisine proper names. The purpose of this research is to find out how Sundanese people name their food through the mental lexicon that appeared in the Sundanese traditional cuisine proper name. The proper cuisine names are collected from Sukabumi, Garut, and Bandung restaurants. The research method applied is a qualitative one. Through a Cognitive Linguistic study, the researchers investigated the phonological sounds and morphological processes that appeared in the Sundanese cuisine proper names. The research revealed that the two and three-vowel sound combinations appear in the proper Sundanese food names through conceptualization in cognitive linguistics. Furthermore, the acronym also happens in this food’s proper names, considering the sound that could produce the exciting names. The research results show that names from the Javanese region experience changes. Sundanese people add the morpheme into the first syllables since Sundanese people are not familiar with two syllables. To conclude, Sundanese people name their food based on how the body reacts to a specification. The form of Sundanese food’s proper name comes from the vowel sounds, which experience a morphemic process—the vocal sounds result in the rhyme. The consonant also tends to form a conceptual meaning that needs further discussion. The resulting research is also beneficial for learning the Sundanese language.